The Determinants of Capital Adequacy Ratio: The Case of the Vietnamese Banking System in the Period 2011-2015 - Pham, Thi Xuan Thoa (H. : ĐHQGHN, 2017)
The analysis of a data set of observations for Vietnamese banks in the period 2011-2015 shows how the Capital Adequacy Ratio (CAR) is influenced by selected factors, namely: asset of the bank SIZE, loans in total assets LOA, leverage LEV, net interest margin NIM, loans lost reserve LLR, Cash and Precious Metals in total assets LIQ. Results indicate, based on data, that NIM and LIQ have significant effect on CAR. On the other hand, SIZE and LEV do not appear to have significant effect on CAR. Variables NIM, LIQ have positive effect on CAR, while variables LLR and LOA are negatively related with CAR